(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Histoarchitecture effect of cypermethrin (pyrethroids) was investigated in the ovary of Stinging catfish, Shing (Heteropneustes fossilis) over a 96 h exposure period as an endpoint of toxicity. The fish were exposed to five acute concentrations (0.00ml/L, 0.025ml/L, 0.050ml/L, 0.075ml/L and 0.10ml/L) and the 96 h LC50 was 0.075 ml/L. The abnormal behavioural patterns noticed in the treated fish were erratic swimming, respiratory distress, discolorations of the skin, loss of reflex, hyperactivities, increasing opercula ventilation and excessive accumulation of mucus on the skin. There was an atretic follicle, cytoplasmic liquefaction, degeneration ovarian wall, invasion of granulosa layer and small inter-follicular spaces after treatment of 0.025 mg/L cypermethrin. Vacuolization at periphery, complete or partial rupture of maturing oocytes, vacuolization of oocytes, degenerating oocytes with disintegrated nuclei and alteration in structure were observed for 0.1 mg/L. The findings of this histoarchitecture analysis of ovary indicate a direct correlation between cypermethrin exposure and the histoarchitecture disorders. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 47-53